COMMUNICATION PHENOMENA ON THE FAMILY ADOPTING THE CHILDREN OF CHINESE RACE IN PEKANBARU - Aldita Khairunnisa; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Adopting children is nothing new in our lives. Each marriage couple would want the presence of a child as the successor of his family that will be educated and raised in the best way. Indonesian people since the past have never been separated from the chinese race people, in this case they lives in harmony as citizens of Indonesia. In Pekanbaru can be found some marriage couples who adopts a chinese race child even though they are also have a biological child in the family. This study aims is to reveal the experience of communication in these families that adopt chinese child. The type of research is descriptive qualitative with phenomenology approach. Based on field facts through observation, in-depth interviews documentation. The research subjects of the families who adopted the chinese race child were from 3 families who also had their biological children from their marriage. This study focuses on exploration in the informant's communication experience. For the purposes of this study are proposed the following three questions: (1) what is the motive of the couple adopting chinese race children (2) How does this family interpret the adoption of chinese children (3) How do they experience their communication in the family with different adopted race children. The results of this study indicate the motives of the family who adopted chinese race child in Pekanbaru consists of because motive which is they are familiar to the chinese race, feel able to educate and raise, having sympathy and empathy. While the motive for in order to motive is to be a muslim chinese, to avoid conflict with the adopted native family, gives love and affection. The meaning given by the growing families who adopted chinese children they live in is destiny to be grateful and add diversity in the family. While the meaning that the perpetrator given generally is differences of religion is something that is only done by capable families and something that can be emulated. The communication experience is categorized into two, which is a fun communication experience and unpleasant communication experience from relatives and the family environment it self. Keywords: Communication Phenomenon, Adoption, Chinese Race